1977
DOI: 10.1111/j.1365-3083.1977.tb00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity of Lymphocytes from Atopic Individuals to Histamine‐Induced Suppression

Abstract: Histamine depressed lymphocyte reactivity to phytohemagglutinin and, to a lesser degree, concanavalin A, when administered simultaneously with mitogen to lymphocyte Cultures. Addition of histamine at later times to the cultures appeared to have a slightly enhancing effect on the lymphocyte response. Stimulation of lymphocytes with pokeweed mitogen was in some CMM enhanced, even by high concentrations of Lymphocytes. Lymphocytes from atopic individuals were more sensitive to the inhibitory effect of histamine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a number of experimental systems in vitro, the activity of lymphoid cells was shown to be affected by treatment with histamine or histamine H2-receptor agonists/antagonists. These systems include antigenor mitogen-induced lymphtocyte proliferation (Strannegard & Strannegard, 1977;Wang & Zweiman, 1978;Brostoff etal., 1980;Hebert et al, 1980;Ogden & Hill, 1980;Suzuki & Huchet, 1981), lymphocyte-mediated cytotoxicity in different systems (Plaut et al, 1975;Schwartz et al, 1980;1981), production of migration inhibition factor (Rocklin, 1976), and antibody production (Lima & Rocklin, 1981;Szewczuk, et al, 1981). Strannegard & Strannegard (1977) also showed that lymphocytes from atopic individuals are more sensitive to inhibition of PHA-induced thymidine incorporation by histamine than cells from normal individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of experimental systems in vitro, the activity of lymphoid cells was shown to be affected by treatment with histamine or histamine H2-receptor agonists/antagonists. These systems include antigenor mitogen-induced lymphtocyte proliferation (Strannegard & Strannegard, 1977;Wang & Zweiman, 1978;Brostoff etal., 1980;Hebert et al, 1980;Ogden & Hill, 1980;Suzuki & Huchet, 1981), lymphocyte-mediated cytotoxicity in different systems (Plaut et al, 1975;Schwartz et al, 1980;1981), production of migration inhibition factor (Rocklin, 1976), and antibody production (Lima & Rocklin, 1981;Szewczuk, et al, 1981). Strannegard & Strannegard (1977) also showed that lymphocytes from atopic individuals are more sensitive to inhibition of PHA-induced thymidine incorporation by histamine than cells from normal individuals.…”
Section: Introductionmentioning
confidence: 99%
“…These systems include antigenor mitogen-induced lymphtocyte proliferation (Strannegard & Strannegard, 1977;Wang & Zweiman, 1978;Brostoff etal., 1980;Hebert et al, 1980;Ogden & Hill, 1980;Suzuki & Huchet, 1981), lymphocyte-mediated cytotoxicity in different systems (Plaut et al, 1975;Schwartz et al, 1980;1981), production of migration inhibition factor (Rocklin, 1976), and antibody production (Lima & Rocklin, 1981;Szewczuk, et al, 1981). Strannegard & Strannegard (1977) also showed that lymphocytes from atopic individuals are more sensitive to inhibition of PHA-induced thymidine incorporation by histamine than cells from normal individuals. In most of these systems histamine has also to be added in the initial part of the reaction to exert its effect; furthermore, inhibition is generally only partial.…”
Section: Introductionmentioning
confidence: 99%